THE ROLE OF MILITARY POLICE IN THE SLOVAK SYSTEM OF INTERNAL SECURITY. RESEARCH REPORT - Jacek Dworzecki (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The aim of the paper is to present results of research on social and expert perception of Military Police in the Slovak Republic. In addition to the research results the paper also features detailed description of the Slovak internal security system including all its formations, history and modern structure.